Taking compliance seriously - Armour, J; Gordon, J; Min, G (Yale Law School, 2019)
How can we ensure corporations play by the “rules of the game”—that is, laws encouraging firms to avoid socially harmful conduct? Corporate compliance programs play a central role in society’s current response. Prosecutors give firms incentives—through discounts to penalties—to implement compliance programs that guide and monitor employees’ behavior. However, focusing on the incentives of firms overlooks the perspective of managers, who decide how much firms invest in compliance.